Primary and Re-exposure effects of D-enantiomeric peptide on metabolism, diversity, and composition of oral biofilms at different stages of recovery - Mohamed Amhmed; Brandon Kieft; Abdullah Almegbel; Lari Häkkinen; Markus Haapasalo; He Liu; Ya Shen (Bioactive Materials)
The persistence of bacteria in the root canal system is the primary cause of recurrent apical periodontitis. The adaptability of residual bacteria to changing environmental conditions is a key survival strategy of biofilms, often leading to endodontic treatment failure. DJK-5 is a protease-resistant, broad-spectrum D-enantiomeric peptide that degrades or prevents the accumulation of guanosine penta- and tetraphosphates, which are important for biofilm formation. We evaluated the effects of primary antimicrobial agents and nutrient conditions on the recovery, metabolism, diversity, and composition of oral biofilms, and investigated how these factors affect the efficacy of DJK-5 and chlorhexidine (CHX) during re-exposure. Primary irrigants and nutrient conditions significantly influenced biofilm recovery, metabolic activity, diversity, and composition. Biofilm recovery was slower in nutrient-poor groups compared to nutrient-rich ones, and nutrient availability had the greatest effect on shaping both the diversity and composition of the biofilms. Water and DJK-5 groups showed similar biofilm diversity trends, while CHX generally led to lower diversity. Results indicate that primary irrigants and nutrient conditions significantly impact biofilm composition, diversity, and recovery. However, these changes did not compromise DJK-5's effectiveness in killing of biofilm microbes during re-exposure of recovered biofilms.